SIKAP KERJA DAN KElUHAN NYERI PINGGANG PAOA PEKERlA KULI PANGGUl 01 PASAR NGRONGGO KOTA KEDIRI TAHUN 2014 - Alfian Adi Priya Kusuma; Sigit Gunawan; Trimawan H. W (GEMA LINGKUNGAN KESEHATAN, 2014)
Porters' main activities involve manual work of hauling material s, dominated by a lifting - carryingactivities Manual Material Handling. Porters operate not in accordance with the rules of good manual work, tend to ignore various aspects of health and safety. Non ergonomical working attitude remains to be afactor that may lead to incidence of low back pains (LBP). Other factors that also contribute to LBPareworkloads, hauling frequency, frequency of breaks and work proportions. The purpose of this study was toillustrate porters' work attitude and their complaints of low back pain at Ngronggo market in Kediri.This was a descriptive study, data were gathered through observations, interviews and measurements ofpain using Nordic Body Map. The population under study was as many as 30 workers operating inNgronggo Market Kediri.From the results of the study in Ngronggo Market Kediri the study discovered that complains of back painwere as many as 26 people ( 86.7 % ). It seemedthat workers implemented the principles regarding bodyposition in the lifting and transporting of goods, but nevertheless complaints of low back pain, and pain injoints still occur.The study recommended that regular schedule of working hours should be made, to avoid overload andcontrol work duration, workers should wear protective girdles at work, and observe proper work attitude.